PASAR MODAL SYARI’AH : INVESTASI SAHAM SYARI’AH ALTERNATIF PENDAPATAN - Wina Paul; Sherly Lisviana (AL-INTIFA, 2023)
This research study is to discuss and analyze the capital market in this case focusing on investment and Islamic stocks, where this stock investment can be an alternative income other than income earned from work or what is called a salary. This research uses qualitative research with descriptive analysis approach. The type of data used in this study is secondary data collected through the literature study method. The analysis used in this research is qualitative analysis. The results of this study show how stock investment can increase income, so that there is a change in mindset about looking for work and getting a salary. Investment is the activity of placing capital in the form of money or other valuable assets into an object, institution or party with the hope that the investor or investor will benefit after a certain period of time. There are many types of investments that can be developed to earn income, one of which is sharia shares. So that income from sharia shares can increase income so that it will change the mindset and mindset of the next generation about investing in sharia shares.